WASP-South hot Jupiters: WASP-178b, WASP-184b, WASP-185b, and WASP-192b. Issue 1 (30th September 2019) - Hellier, Coel; Anderson, D R; Barkaoui, K; Benkhaldoun, Z; Bouchy, F; Burdanov, A; Cameron, A Collier; Delrez, L; Gillon, M; Jehin, E; Nielsen, L D; Maxted, P F L; et al.
ABSTRACT: We report on four new transiting hot Jupiters discovered by the WASP-South survey. WASP-178b transits a V  = 9.9, A1V star with T eff  = 9350 ± 150 K, the second-hottest transit host known. It has a highly bloated radius of 1.81 ± 0.09  R Jup, in line with the known correlation between high irradiation and large size. With an estimated temperature of 2470 ± 60 K, the planet is one of the best targets for studying ultrahot Jupiters that is visible from the Southern hemisphere. The three host stars WASP-184, WASP-185, and WASP-192 are all post-main-sequence G0 stars of ages 4–8 Gyr. The larger stellar radii (1.3–1.7 M⊙ ) mean that the transits are relatively shallow (0.7–0.9 per cent) even though the planets have moderately inflated radii of 1.2–1.3  R Jup . WASP-185b has an eccentric orbit ( e  = 0.24) and a relatively long orbital period of 9.4 d. A star that is 4.6 arcsec from WASP-185 and 4.4 mag fainter might be physically associated.